Memorial University folklore students, Clara and Sherman sit next to Émile Benoit who plays the fiddle at his house as his daughter looks on - Murphy, Clara (1983)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial : « Sheep, Slipways and Other Aspects of Traditional French Newfoundland Culture ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "Sheep, Slipways and Other Aspects of Traditional French Newfoundland Culture".